2013
DOI: 10.1002/chem.201303683
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific, Regioselective Cross‐Coupling Reactions of Secondary Allylic Boronic Esters

Abstract: An original­ syn: The first enantioselective Suzuki–Miyaura cross‐coupling of chiral, enantioenriched secondary allylic boronic esters is described (see scheme; DME=dimethoxyethane, Bpin = pinacolboryl, dba = dibenzylideneacetone). Mechanistic studies show that the reactions proceed via γ‐selective transmetalation followed by reductive elimination. The reaction provides the first independent confirmation that the transmetalation of boronic esters proceeds via a syn pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 52 publications
5
42
0
1
Order By: Relevance
“…The ensuing transmetallation may occur through either an S E or S E 0 mechanism. The S E 0 mode of transmetallation is thought to be prevalent with phosphine-ligated Pd(II) species 25,29 . Thus, in these conditions, both XPhos and (4-CF 3 -C 6 H 4 ) 3 P are expected to first provide s-bonded allylic Pd(II) complex B via a syn-S E 0 pathway made favourable through coordination of the electron-deficient Pd(II) to the electron-rich alkene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ensuing transmetallation may occur through either an S E or S E 0 mechanism. The S E 0 mode of transmetallation is thought to be prevalent with phosphine-ligated Pd(II) species 25,29 . Thus, in these conditions, both XPhos and (4-CF 3 -C 6 H 4 ) 3 P are expected to first provide s-bonded allylic Pd(II) complex B via a syn-S E 0 pathway made favourable through coordination of the electron-deficient Pd(II) to the electron-rich alkene.…”
Section: Discussionmentioning
confidence: 99%
“…With allylic boronates, the challenge of controlling selectivity is aggravated by the need to address a third type of selectivity arising from the possibility of forming two different regioisomers (Fig. 1c) [22][23][24][25][26][27][28][29] . Regioisoselectivity (or 'site selectivity') tends to be governed by the intrinsic steric and electronic effects dictated by the allylic substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Along similar lines, in 2013, Chausset‐Boissarie et al . described the regioselective SM cross‐coupling reaction starting with secondary allylic boronate ester ( E )‐ 116 (Scheme ).…”
Section: Suzuki‐miyaura Cross‐coupling Reactionmentioning
confidence: 87%
“…Furthermore, upon subjection of a branched boronate 40 and a linear boronate 41 to the reaction conditions in a competitive situation, it was observed that there was a complete selectivity for the branched boronate, an indication that there is an important role imparted upon the benzylic nature of the boronate functionality (Scheme 9b). Recently, it was found that these reaction conditions can also be applied towards the stereospecific cross-coupling of optically enriched allylic and propargylic boronates [70]. In a later report [71], it was found that the amount of triphenylphosphine had a direct impact on both the yield and stereochemical outcome of the reaction.…”
Section: Stereoselective Couplings Of Alkyl Boronates With Aryl or Almentioning
confidence: 99%